2016
DOI: 10.1002/qua.25312
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for the Slater exchange potential and its performance for solids

Abstract: A simple local model for the Slater exchange potential is determined by least square fit procedure from Hartree-Fock (HF) atomic data. Since the Slater potential is the exact exchange potential yielding HF electron density from Levy-Perdew-Sahni density functional formalism (Levy et al., Phys. Rev. A 1984, 30, 2745), the derived local potential is significantly more negative than the conventional local density approximation. On the set of 22 ionic, covalent and van der Waals solids including strongly correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 44 publications
(79 reference statements)
0
34
0
Order By: Relevance
“…All these LDA and GGA potentials are obtained as functional derivative v xc = δ E xc /δρ of energy functionals. The LDA consists of the exchange 2 and correlation 39 of the homogeneous electron gas, while Sloc (acronym for local Slater potential 30 ) consists of a slightly modified but strongly enhanced exchange LDA ( v x Sloc = −1.67ρ 0.3 compared to v x LDA ≃ −0.7386ρ 1/3 ) with no correlation added. The GGAs are the exchange-correlation PBE from Perdew et al, 13 the exchange of Engel and Vosko 40 (EV93PW91, combined with correlation from Perdew and Wang 41 as done in ref ( 42 )), the exchange from Armiento and Kümmel 28 , 37 , 38 (AK13, no correlation added as done in refs ( 28 ) and ( 37 )), and the recently proposed HLE16 17 that consists of a modification of the HCTH/407 functional 43 (the exchange and correlation components are multiplied by 1.25 and 0.5, respectively).…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these LDA and GGA potentials are obtained as functional derivative v xc = δ E xc /δρ of energy functionals. The LDA consists of the exchange 2 and correlation 39 of the homogeneous electron gas, while Sloc (acronym for local Slater potential 30 ) consists of a slightly modified but strongly enhanced exchange LDA ( v x Sloc = −1.67ρ 0.3 compared to v x LDA ≃ −0.7386ρ 1/3 ) with no correlation added. The GGAs are the exchange-correlation PBE from Perdew et al, 13 the exchange of Engel and Vosko 40 (EV93PW91, combined with correlation from Perdew and Wang 41 as done in ref ( 42 )), the exchange from Armiento and Kümmel 28 , 37 , 38 (AK13, no correlation added as done in refs ( 28 ) and ( 37 )), and the recently proposed HLE16 17 that consists of a modification of the HCTH/407 functional 43 (the exchange and correlation components are multiplied by 1.25 and 0.5, respectively).…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…Thus, the search for a fast semilocal and reliable DFT method for electronic structure calculation, more particularly for band gaps, is of very high interest. 26 30 …”
Section: Introductionmentioning
confidence: 99%
“…The results of calculations with the GLLB-SC potential on various properties will be compared to those obtained with other multiplicative potentials of the LDA, GGA, or meta-GGA (MGGA) type, which are the following. The LDA 2,67 is exact for the homogenous electron gas, while Sloc (abbreviation for local Slater potential 31 32 which is a modification of HCTH/407 70 (the exchange and correlation components are multiplied by 1.25 and 0.5, respectively). Note that all GGA potentials depend on ρ σ and its first two derivatives, while the xc potential LB94 of van Leeuwen and Baerends, 71 also considered in the present work, depends only on ρ σ and its first derivative.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the present work is to provide a further contribution in this conceptual direction. It has recently been shown that chemical bonding of increasing accuracy can be obtained from non-parameterized, ab initio, orbital-free methods [ 52 , 53 , 54 ] via the bifunctional approach [ 52 , 53 , 54 , 55 , 56 , 57 ] (exploiting the homogenous scaling behavior of the functionals [ 58 ]), and the introduced atomic fragment approximation [ 52 , 53 , 54 , 56 , 57 ]. The target of the present study is to shed some light on potential systematic pathways beyond the atomic fragment approximation.…”
Section: Introductionmentioning
confidence: 99%